Physiological processes associated with genetic progress in yield potential of wheat (Triticum aestivum L.) - Aisawi, Khaled A. Boulgasem (2012)
Wheat (Triticum aestivum L.) is the most widely grown of any crop and provides one-fifth of the total calories of the world's population. Since the 1960s, increases in productivity have been achieved as a result of wide-scale adoption of Green Revolution technologies. However, in spite of growing demand, the challenges of increasing production to feed an estimated world population of 9 billion in 2050 are still considerable. Due to the increased demand, it is estimated that food production must be increased by about 50% by the year of 2050. Improving wheat productivity through developing cultivars with high yield potential and with high adaptability to specific environments is the key objective in the wheat breeding programs worldwide to fill the gap between the production and the demand. The overall aims of the present study were to: (i) investigate the physiological basis of yield potential progress from 1966 to 2009 in spring bread wheats released at the International Center for Maize and Wheat Improvement (CIMMYT) in the irrigated high potential environment of NW Mexico, (ii) investigate the physiological basis of effects of the tiller inhibition Tin1A gene on ear-fertility traits and yield potential and interactions with plant density in NW Mexico and UK environments in lines of a doubled-haploid (DH) population segregating for Tin1A/non-Tin1A alleles and (iii) identify breeding targets for new cultivars with higher yield potential.